2009
DOI: 10.1210/me.2008-0357
|View full text |Cite
|
Sign up to set email alerts
|

p54nrb Is a Transcriptional Corepressor of the Progesterone Receptor that Modulates Transcription of the Labor-Associated Gene, Connexin 43 (Gja1)

Abstract: The progesterone receptor (PR) plays important roles in the establishment and maintenance of pregnancy. By dynamic interactions with coregulators, PR represses the expression of genes that increase the contractile activity of myometrium and contribute to the initiation of labor. We have previously shown that PTB-associated RNA splicing factor (PSF) can function as a PR corepressor. In this report, we demonstrated that the PSF heterodimer partner, p54nrb (non-POU-domain-containing, octamer binding protein), can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 69 publications
2
55
0
Order By: Relevance
“…For example, NonO binds to the DNA-binding domain of steroid hormone receptors and suppresses transcriptional activity in the absence of hormone ligand. (Dong et al, 2009). In contrast to the many reported repressive effects, NonO has a transcriptional coactivator function in androgen receptor-mediated transcription (Ishitani et al, 2003;Kuwahara et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…For example, NonO binds to the DNA-binding domain of steroid hormone receptors and suppresses transcriptional activity in the absence of hormone ligand. (Dong et al, 2009). In contrast to the many reported repressive effects, NonO has a transcriptional coactivator function in androgen receptor-mediated transcription (Ishitani et al, 2003;Kuwahara et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…It has also been shown that p54nrb acts as transcriptional repressor to regulate Connexin-43 expression when it interacts with the progesterone receptor during the labour (Dong et al, 2009), or with the Malignant Inhibitor Activity (MIA) in melanoma progression (Schiffner et al, 2011). Interestingly, (Amelio et al, 2007) showed that p54nrb is implicated in transcription regulation of c-fos mediated by CREB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, P 4 /PRcan exert a pronounced anti-inflammatory effect, by inhibiting activation/DNA binding of the proinflammatory transcription factors, NF-kB ) and AP-1 (Dong et al 2009). Alternatively, P 4 /PR can block induction of the proinflammatory response by up-regulating expression of the NF-kB inhibitor, IkBa , and the mitogen-activated kinase (MAPK) inhibitor, MAPK phosphatase-1 (MKP-1), also known as dual specificity phosphatase 1 (DUSP1) (Chen etal.…”
Section: Mechanisms For P 4 /Pr Regulation Of Myometrial Quiescencementioning
confidence: 99%